Does Teacher Subject Knowledge Contribute to Student Academic Performance in Developing and Least Developed Countries? - Marcenaro-Gutiérrez, Óscar David; López-Agudo, Luis Alejandro (Wiley, 2020)
Little is known about the causal impact of teacher knowledge on student performance. In this research paper we intend to approach the potential causal effect (i.e. going beyond correlation) of sixth grade teachers’ knowledge on their students’ academic achievement for three Sub-Saharan African countries. To achieve this, we have used the heterogeneity of teachers’ subject knowledge and students’ correspondent academic achievement within-student between-subjects using student fixed effects. Concretely, our work is based on previous research by Bietenbeck, Piopiunik and Wiederhold. Compared to them, we do not use countries that lack representative information after keeping only those students taught by the same teacher for the subjects under analysis. This enables us to obtain more reliable results on this issue. Our results indicate that teacher subject knowledge in reading and mathematics does not have a significant influence on student academic achievement in these subjects for the countries under scrutiny. Many robustness checks have corroborated this conclusion, which contrasts with the positive effect found by Bietenbeck, Piopiunik and Wiederhold.
https://openpolicyfinder.jisc.ac.uk/id/publication/6969
Keywords: Profesores - Formación profesional; Rendimiento académico; Relaciones profesor-alumno; Educación - Aspectos económicos; Países en desarrollo; developing country; least developed country; student academic achievement; teacher subject knowledge